Isolasi dan Identifikasi Bakteri Asam Laktat Proteolitik dari Susu Kedelai yang Terfermentasi Spontan - Yusmarini, Yusmarini; Indrati, Retno; Utami, Tyas; Marsono, Yustinus (Jurnal Natur Indonesia, 2009)
Lactic acid bacteria is a group of bacteria with proteolytic activities enambling to grow on protein rich substratesuch as soymilk. This research was aim to isolate and identify lactic acid bacteria with have proteolytic activityfrom spontaneous fermented soy milk. Sixteen isolates out of 26 colonies isolated from fermented soymilk arepresumed as lactic acid bacteria. Among these 16 isolates, only 3 of them showed proteolytic activity. These threeisolates were further identify morphologically and only two isolates identified as Lactic Acid Bacteria, namelyR.1.3.2 and R.11.1.2. The ability of these isolates to produce acid and protease were observed. The results showedthat isolate R 1.2.3 higher ability in producing protease.